An investigation of cavitation cooling effect in converging-diverging nozzles - Alkotami, Abdulmalik (Kansas State University, 2014)
A traditional cooling/refrigeration cycle has four main system components which are an evaporator, a compressor, a condenser, and an expansion valve. This type of cycle requires use of refrigerants which have been found to be harmful to the environment, including causing damage to the atmospheric ozone layer. The main objective of the project was to investigate a water-based non-vapor compression cooling system. Water as a working fluid has the advantages of being inexpensive and environmentally safe for use, as compared to commercially available chemical refrigerants. The water-based cooling system investigated employed cavitation phenomena in converging-diverging glass nozzles. Cavitation is an important phenomenon in fluids, and is common occurring in many devices such as pumps, refrigeration expansion valves, and capillary tubes. It occurs when the static pressure of the fluid falls below the vapor pressure, into a metastable liquid state. Cavitation can be in the form of traveling bubble cavitation, vortex cavitation, cloud cavitation, or attached wall cavitation. In this thesis, the focus was first on visualizing cavitation for water flowing through converging- diverging glass nozzles. These nozzles had throat diameters between 2 mm and 4 mm. Two systems were used: (1) a continuous flow system, where water was driven by a centrifugal pump, and (2) a transient blow down system, where water flow was initiated using a suction pump. A high-speed camera was used to record videos and images of the associated cavitation phenomena. A thermal infrared camera was used in an attempt to measure temperature drop in the nozzle while the system was running The second part of this thesis focused on the understanding of the fundamental thermodynamics phenomena and on the development of practical knowledge relevant to the cavitation process. Two equations of state were used in the analysis, the van der walls equation of state, and the Peng Robinson equation of state. Equations of state were used to predict the transition from vapor to liquid. At a given temperature, the equations were solved for a pressure value corresponding to saturated liquid and saturated vapor specific volume values. Then, the equations were used to determine the spinodal liquid and vapor lines, which represent the metastabillity limits for the liquid and vapor. The characteristic equations of state, combined with implementation of the Law of Corresponding States and thermodynamic theory, were used to estimate the temperature reduction available for refrigeration.
Keywords: Cavitation; Converging-diverging; Cooling; Nozzles